1999
DOI: 10.2135/cropsci1999.0011183x003900030038x
|View full text |Cite
|
Sign up to set email alerts
|

Using Geographic Information to Acquire Wild Crop Germplasm for Ex Situ Collections: II. Post‐Collection Analysis

Abstract: Without committing significant resources in the decision‐making process, curators are challenged to identify among newly collected germplasm, exceptional accessions that merit inclusion in ex situ collections. The objectives of this paper were to illustrate how geographic information can be used to infer (i) site uniqueness relative to other sites sampled, (ii) the likelihood that an accession reflects adaptation to the site, and (iii) uniqueness of a given accession relative to other accessions of the same ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…(Chapman & Barreto, 1996;Greene et al, 1999;Grenier et al, 2001;Guarino, et al, 2002). Tal variabilidade é essencial em programas de melhoramento genético.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…(Chapman & Barreto, 1996;Greene et al, 1999;Grenier et al, 2001;Guarino, et al, 2002). Tal variabilidade é essencial em programas de melhoramento genético.…”
Section: Resultsunclassified
“…Atualmente, a Embrapa Cerrados possui um banco com mais de 1.400 acessos do gênero Stylosanthes, sendo 136 S. macrocephala, com alto potencial em programas de melhoramento genético, conforme avaliações realizadas na Embrapa Cerrados (Andrade et al, 2004). A caracterização genética dos acessos é essencial para determinar o grau de variabilidade das coleções, enquanto características ecogeográficas dos pontos de coleta permitem inferir possíveis vantagens adaptativas de cada acesso (Chapman & Barreto, 1996;Greene et al, 1999;Guarino et al, 2002). Ambas as informações orientam os programas de coleta e fornecem subsídios para a seleção do material adequado ao trabalho de melhoramento genético (Jarvis et al, 2003).…”
Section: Introductionunclassified
“…We considered values above 0.8 as very strong, between 0.6 and 0.8 as strong, between 0.4 and 0.6 as moderate, between 0.2 and 0.4 as weak, and between 0 and 0.2 as very weak. Greene et al (1999aGreene et al ( , 1999b demonstrated the utility of geographic information systems (GIS) analysis, combining physical distance and environmental data, in exploring sampling protocols. We tested associations of disease and pest resistances to climatic variables following our same methodologies in Jansky et al (2006Jansky et al ( , 2008.…”
Section: Methodsmentioning
confidence: 99%
“…Interpolated climate surfaces can also be used to characterize conditions at each collection site given its latitude, longitude and altitude, for example using FLORAMAP. Steiner and Greene (1996) describe this process as 'retro-classification' of accessions and give an example of its usefulness using the Lotus collection of the US National Plant Germplasm System (NPGS) (see also Greene et al, 1999b).…”
Section: Germplasm Targetingmentioning
confidence: 99%